The Relation of Meteorological Elements with AOD for Building Energy Consumption - Hong Soo Lim; Gon Kim (Advances in Meteorology)
This study presents statistical relationships between various meteorological elements in Seoul city. It also discusses the vitality of the obtained relationship on the modelling of building energy consumption. The data utilized in statistical evaluations was obtained from the archives of the Korean Meteorological Agency (KMA) for a period of four years. Another set of data was derived from state-of-the-art equations. The used elements aside from aerosols are used for analysis in building energy simulations. For each weather element in the study, frequency and a monthly average are presented. Furthermore, statistical correlations are presented: solar radiation and temperature, solar radiation and sky cover, and solar radiation and aerosol optical depth (AOD). The results indicate that the common assumption of a direct relationship between temperature and solar radiation is rather incorrect. In addition, whereas high solar altitudes are usually associated with high levels of solar radiation, the obtained results indicate a relatively weak relationship between the two variables (R2 = 0.463). The obtained results are proof that the effect of meteorological elements on, say, a building is not a single direct effect from a single variable but rather a combination of relationships between variables, which then produce a single effect.